Interpreting spatially explicit variation in dietary proxies through species distribution modeling reveals foraging preferences of mammoth (Mammuthus) and American mastodon (Mammut americanum) - Pardi, Melissa I.; DeSantis, Larisa R. G. (Frontiers in Ecology and Evolution, 2022)
The end Pleistocene was a time of considerable ecological upheaval. Recent work has explored the megafauna extinction’s role in altering ecosystem processes. Analyses of functional traits withing communities reveal hidden consequences of the megafauna extinction beyond declines in taxonomic diversity. Functional diversity analyses offer new insight into our understanding of past ecosystems and may even inform future rewilding efforts. However, the utility of functional diversity may be hampered by the use of discrete, taxon-level functional traits, such as dietary categories, that mask variation in functional diversity over space and time. Here, we present an approach in which species distribution modeling, in Maxent, provides context for interpreting variation in two widely used proxies for diet among fossil taxa: stable isotope analysis and dental microwear texture analysis. We apply this approach to two ecologically distinct taxa, the American mastodon (Mammut americanum) and mammoths (Mammuthus) and investigate their resource use over space and time from the last glacial maximum to the end Pleistocene (25-11.7 thousand years before present). Mammoth dietary behavior varies by context across their geographic distribution, despite possessing evolutionary adaptations that facilitate grazing. Mammoths exhibit a preference for grazing where species distribution modeling predicts the highest likelihood of occurrence but engage in more mixed-feeding outside of core likelihood areas. In contrast, dietary preferences for mastodon are less resolved and our analyses were unable to identify significant differences in diet across their distribution. The ecological roles of some species are context specific and need to be critically evaluated when planning for management of reintroductions or introducing novel species to restore lost ecological function.